System Design Considerations for Automated Health Screening - Henderson, C. (Methods of Information in Medicine, 1974)
The current trend in health care indicates that future multiphasic screening systems may require automated decision-making techniques in order to accommodate the attendant problems of screening system load, screening test accuracy, and disease prevalence among the population being screened. This paper discusses a methodology for on-line classification of patients by means of the medical history questionnaire. The work presented indicates that the dynamic characteristics of an automated screening system can be enhanced through the use of trainable pattern classifiers and automatically adjusted screening thresholds.
Keywords: Multiphasic Screening; System Design; Questionnaire; Automated Pattern Classifier